2010
DOI: 10.1161/circresaha.109.206334
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Triggers Subcellular Compartmental Redox Signaling in Vascular Smooth Muscle Cells

Abstract: Key Words: mitochondria Ⅲ reactive oxygen species Ⅲ ratiometric fluorescent protein sensor Ⅲ hypoxic pulmonary vasoconstriction S mall pulmonary arteries constrict in response to a decrease in alveolar oxygen tension through a physiological response termed hypoxic pulmonary vasoconstriction (HPV). Despite intensive study since the first description of HPV in 1946, the mechanism of O 2 sensing remains unclear. Mitochondria have been considered a putative site of cellular oxygen sensing because they consume O 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
368
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 327 publications
(396 citation statements)
references
References 55 publications
25
368
1
2
Order By: Relevance
“…In contrast, oxidation in the mitochondrial matrix decreased from 46.1 6 2.9% during normoxia to 21.7 6 2.3% after 30 minutes of hypoxia ( Figure 1C). These results in mouse PASMC are consistent with previous results obtained in rat PASMC (10).…”
Section: Hypoxia Increases Ros In the Ims And Cytosol And Decreases Rsupporting
confidence: 93%
See 4 more Smart Citations
“…In contrast, oxidation in the mitochondrial matrix decreased from 46.1 6 2.9% during normoxia to 21.7 6 2.3% after 30 minutes of hypoxia ( Figure 1C). These results in mouse PASMC are consistent with previous results obtained in rat PASMC (10).…”
Section: Hypoxia Increases Ros In the Ims And Cytosol And Decreases Rsupporting
confidence: 93%
“…Some of the results of these studies have been previously reported in the form of abstracts (30,31).…”
Section: What This Study Adds To the Fieldmentioning
confidence: 89%
See 3 more Smart Citations